How Good at Neurology are you? – Answers. Issue 4 (1st August 2004) - Goldsmith, Paul; Lennox, Graham; Ray, Julian
Abstract : 1. Anarteriovenous malformation(AVM).Serpiginous flow voids are seen within the interhemispheric fissure on the sagittal T1-weighted image. Additional vascular structures are seen on the T2 axials lying around the brainstem and quadrigeminal cistern. In this particular case the AVM was situated in the dura, with occlusion of the right sigmoid, superior sagittal and straight sinuses, as well as stenosis of the left transverse sinus (Fig. 1). This oblique view of a selective left occipital angiogram demonstrates a dural arteriovenous fistula involving the left transverse sinus, as well as stenosis of the sinus. A CT may show areas of calcification in an irregular mass with large associated veins and arteries. A flow void is seen on MRI because of the rapidity of blood flow. Patients may present with symptoms due to compression or a steal phenomenon, or through haemorrhage. Haemorrhages secondary to an AVM are less severe than those due to ruptured